1988
DOI: 10.1111/j.1467-8624.1988.tb03681.x
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Response to Auditory Stimulus Discrepancy

Abstract: Newborns were assessed for their recovery of head turning toward laterally presented auditory stimuli (titi) that varied from a familiar standard on 1 of 5 levels of fundamental frequency. Following habituation to repeated standard trials, newborns recovered to 14% and 21%, but not to 0%, 7%, or 28% discrepancies, indicating that recovery was a quadratic function of the degree of stimulus-schema discrepancy. Moreover, newborns reliably turned away from the standard stimulus during posthabituation no-change con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1989
1989
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…The auditory information processing procedure used in this study has been shown to elicit a reliable pattern of responding among neonates in numerous well-controlled studies. [37][38][39][40][41][42][43]45 Using this procedure, newborn infants consistently demonstrate orientation and habituation to an auditory familiarization stimulus and recovery to a novel auditory stimulus. Moreover, recovery to novelty was shown to discriminate between neonates at high-, moderate-, and low-risk for subsequent developmental delay 37 indicating that the procedure has good discriminant validity and is, therefore, appropriate for assessing the effects of intrauterine cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The auditory information processing procedure used in this study has been shown to elicit a reliable pattern of responding among neonates in numerous well-controlled studies. [37][38][39][40][41][42][43]45 Using this procedure, newborn infants consistently demonstrate orientation and habituation to an auditory familiarization stimulus and recovery to a novel auditory stimulus. Moreover, recovery to novelty was shown to discriminate between neonates at high-, moderate-, and low-risk for subsequent developmental delay 37 indicating that the procedure has good discriminant validity and is, therefore, appropriate for assessing the effects of intrauterine cocaine exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the information processing procedure developed by Zelazo and colleagues [37][38][39][40][41][42][43]45 was used to assess newborn central processing of auditory stimuli. It was hypothesized that cocaine exposure in utero can alter neurologic development and this may be detected at birth by abnormal auditory information processing.…”
mentioning
confidence: 99%
“…After habituation, the infants heard either the same word or one of the four variations created by altering the fundamental frequency of the original sound by 7%, 14%, 21%, or 28%. The infants were most likely to orient to a stimulus that altered the fundamental frequency by 14% or 21% (moderate discrepancies) and less likely to orient to the more extreme alteration (Weiss, Zelazo, & Swain, 1988; see also Fenwick & Morrongiello, 1998; Saffran, Loman, & Robertson, 2000). Three‐week‐olds looked longer at 2 × 2 checkerboards than at 8 × 8 and 24 × 24 designs; 8‐week‐olds looked longest at 8 × 8 checkerboards; and 14‐week‐olds stared longest at the 24 × 24 forms (Brennan, Ames, & Moore, 1966).…”
Section: A Trio Of Influences On Lookingmentioning
confidence: 99%
“…Finally, some aspects of stimulus change are more likely to capture the subject's attention than others, suggesting that infants may differentially weight stimulus features. Recovery of the orienting response in infants has been elicited by a variety of stimulus changes, including a change in the intensity of a tone burst (43), an altered rattle sound (50), a new pulsed synthetic vowel (48), a change in the initial consonant of a syllable (51), and a new two syllable nonsense word (52). One study (53) presented 6-month-old infants with a pair of tones (400 Hz -1000 Hz) as habituating stimuli.…”
Section: Orientingmentioning
confidence: 99%